Comparison between different veneering methods on failure of zirconia restorations; A review - Hoseinali Mahgoli; Somayeh Allahyari (Tehran University of Medical Sciences, 2018)
In recent years, the use of zirconia as a high-strength support for all-ceramic restorations has become widely accepted. The failure of zirconia restorations is mainly due to the weakness of veneering porcelain and other factors such as veneering approach. Except conventional hand layering, other methods such as pressing and digital veneering have been recently introduced and used. Meanwhile, the use of monolithic zirconia with no veneer is also a solution for reducing the rate of failure. The object of this review was to compare the failure of three available methods for veneering zirconia restorations in the literature and to compare with the monolithic zirconia. In the context of this overview, 42 articles were used between the years 2000 through the end of 2016 using the keywords of PubMed, google scholar search engines. In most articles, digital approach is the best way with low failure. mechanical properties of monolithic zirconia are reported to be higher than the zirconia veneered using hand layering method.